Vibrational Frequencies of Water Isotopologues : Vibron Model - J. Vijayasekhar; M. V. Subba Rao (International Journal of Mathematics And its Applications, 2017)
In this paper, calculated vibrational frequencies of water isotopologues, Deuterium oxide ($D_{2}O$), Water-${}^{18}$O ($H_{2}{}^{18}O$) in fundamental level using Hamiltonian expression, which is in terms of invariant and Majorana operators describe stretching vibrations.